Assessment of the neutrophilic antibody-dependent respiratory burst (ADRB) response to Plasmodium falciparum. Issue 6 (12th August 2014) - Kapelski, Stephanie; Klockenbring, Torsten; Fischer, Rainer; Barth, Stefan; Fendel, Rolf
Abstract : Assessment of different ADRB assays to determine their suitability for the evaluation of neutrophil stimulation by antimalarial antibodies. Abstract: Semi-immunity against Pf malaria is based on a combination of cellular and humoral immune responses. PMNs and IgGs are considered important components of this process, but the underlying mechanisms are unclear. We investigated the neutrophilic ADRB by analyzing the production of ROS in response to Pf antigen-specific IgGs bound to solid-phase immobilized antigens (sADRB) or whole merozoites (mADRB). We found that the PMN stimulations in each assay were based on different underlying mechanisms, demonstrating the importance of the assay set-up for the evaluation of antibody-triggered PMN responses. In the sADRB assay, ROS were produced externally, and by specific blocking of CD32(a)/FcγRII(a), the immediate neutrophilic response was abolished, whereas the removal of CD16(b)/FcγRIII(b) had no substantial effect. The key role of CD32(a) was confirmed using CD16(b)-deficient PMNs, in which similar changes of neutrophilic ADRB profiles were recorded after treatment. In the mADRB assay, ROS were produced almost exclusively within the cell, suggesting that the underlying mechanism was phagocytosis. This was confirmed using an additional phagocytosis assay, in which PMNs specifically ingested merozoites opsonized with Ghanaian plasma IgGs, seven times more often than merozoites opsonized with European plasma IgGs ( P <0.001). Our data show that assay set-ups used to evaluate the responses of PMNs and perhaps other effector cells must be chosen carefully to evaluate the appropriate cellular responses. Our robust, stable, and well-characterized methods could therefore be useful in malaria vaccine studies to analyze the antimalarial effector function of antibodies.